Clinical Outcomes Penggunaan Antibiotik pada Pasien Infeksi Kaki Diabetik - Yusi Anggriani; Mita Restinia; Venessya Cikita Mitakda; Rochsismandoko Rochsismandoko; Tri Kusumaeni (Jurnal Sains Farmasi & Klinis, 2015)
An amputation and antibiotic resistant bacteria on diabetic foot infection (DFI) are still big issue. The research aimed to evaluate clinical outcomes of antibiotic use among patients of DFI in internal medicine ward at Hospital X. An observation of prospective longitudinal methode was conducted during 3 months. Patients were selected based on diagnosis of DFI that had length of stay ≥ 3 days. Total samples were 30 patients, 16(53.3%) women and 14(46.7%) men. Only 5(16.67%) patients who did culture and sensitivity. One of them with no pathogen bacteria. The most frequently antibiotic use was ampicillin-sulbactam. Based on clinical outcomes, 11(36,7%) improve, 15(50%) worse, and others were passed away. Based on statistic, there were no influence among clinical outcomes with gender, age, BMI and duration of diabetes. Therefore based on the research, antibiotics use were still not effective to achieve desired outcomes.